(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract: The aim of this research is to highlight the importance of achieving customer satisfaction by using information technology and Internet networks in the process of purchasing flight tickets, and switching from the traditional method of purchasing and payment operations to the electronic method, to reduce the financial and non-financial risks associated with the traditional purchasing process, as well as saving time, effort and costs for the customer. The researcher used the deductive approach in linking the variables (achieving customer satisfaction and Internet of Things technology for booking electronic tickets) with the aim of satisfying the desires and needs of customers (the General Company for Iraqi Airways) from the perspective of adding new services that save the cost of time and money when purchasing tickets for various flights, The researcher also used the inductive approach and conducted a survey of studies that presented the research variables with the aim of extracting ideas and compiling the theoretical foundations presented in books, periodicals, conferences, and relevant research, whether Iraqi, Arab, or foreign. This research shows part of the cognitive foundations of customer satisfaction and Internet of Things technology. As well as surveying the opinions of a group of customers of the General Company for Iraqi Airlines and the results of its statistical analysis, and stating their desires to provide an application for purchasing electronic tickets through their own smart devices.As for the applied aspect and regarding measuring customer satisfaction, reliance was placed on the electronic questionnaire prepared on the Google Forms platform and it was distributed electronically to a group of travelers at Baghdad International Airport at random. The ready-made statistical analysis program (SPSS V.26) was also used to extract: - Measuring the strength of the sample’s response was based on a five-point Likert scale, weighted arithmetic mean, standard deviation, and relative importance. Correlation coefficient and linear regression. The research reached the most important results:The company is weak in exploiting the development in the field of information and communications technology, remote purchasing via the Internet, payment using electronic cards, and the speed of collecting amounts via electronic transfer, as the company still deals with traditional methods of periodic accounting with ticket sales offices.Several recommendations came from the research, the most important of which are:It is necessary for the General Company of Iraqi Airlines to shift to the digital method in flight ticket sales and develop them into electronic tickets by employing Internet of Things technology.